Halal businesses for everybody: big opportunities in store - Abdullah, Moha Asri (2018)
Malaysia has established herself as pioneer of the global halal industry. As a result, Malaysia is ranked as the first Halal Hub Centre in the world nowadays. Halal industry in Malaysia is huge with a size of market totalling to RM250 billion in 2016. With uptrend market, the value is expected to increase to triple in 2030. There are a range of halal industry’s components. It is not merely related to food and beverage. However, it covers a wide spectre of products and services, including food ingredients and feed industries; pharmaceutical cosmetic and personal care products; meat poultry and seafood; farm input and animal feed; Islamic finance and banking; logistic, transport and shipping; tourism and hospitality services, standard, auditing and lab analysis; training and consultancy; research and development. Globally, a total of USD2 billion worth of Halal market in 20916 and is expected to increase to more than USD3 billion by 2022. It is now demanded not only in Muslim countries, but it is also rising demand in traditionally non-Muslim countries. Countries like U.K., France, Germany and the US have strong presence of Halal products and services. Some of Halal products are purposely located at one corners of some big supermarkets in those countries. Higher increasing rate of Muslim population in the world, immigration of the Muslim has resulted in higher demand for Halal products and services around the world. In addition, rate of economic growth and development in many Muslim nations have contributed to this trend, while the increase in purchasing power parity is equally essential. Recent interests from Japan, South Korea, Taiwan and China in Halal products and services, it provides huge opportunities for every stakeholder to leverage on the industry. The paper concludes that if more halal ingredients are made available in the market and effective promotion of Muslim tourism are carried out, a much higher prospect and value of halal industry development could be anticipated.